Formulation of Risperidone Nano Niosomal Vesicular System by Ecofriendly Direct Ultrasonication Method - Al- Shadedi, Mohamed I.; Al_Gawhari, Fatima J. (Iraqi Journal of Pharmaceutical Sciences, 2025)
Risperidone is atypical antipsychotic agent used mainly in treating schizophrenia, it is classified as class II in BCS classification. Nanovesicular system may provide a circumvent to these hurdles. The aim of this study is to develop a physical stable nanovesicular system with improved characteristics by addition of dicetyl phosphate at various concentrations as charge inducing agent. The preparation method was ecofriendly direct sonication. Span 60, cholesterol and drug at a fixed amounts were added to different concentrations of dicetyl phosphate ((0,3,6,12,18, and 24mg)/10 mL) to give six formulations, the final mixtures were added to phosphate buffer saline pH 7.4 and sonicated at 60°C without usage of organic solvents along the process of formulation. Dynamic light scattering, zeta potential, entrapment efficiency percentage, transmission electron microscopy (TEM), and in vitro release were used to assess the characteristics of the formulations. Fourier transform infrared (FTIR) spectra was implemented to investigate possibility of drug-excipients interactions. The particle size range was (193.97±1.85 - 427.23±199.27nm), particle size distribution (PDI) (0.13±0.06 - 0.62±0.10), TEM showed a vesicular shape of the prepared formula, and entrapment efficiency percentage (48.07±0.20 - 87.40±0.33%). Formula containing dicetyl phosphate at concentration (18mg/10ml) showed the lowest mean particle size (193.97nm), lowest mean of PDI (0.13), lowest zeta potential mean (-20.10mV), and entrapment efficiency percentage mean of (50.9%). Furthermore, the release was 68.17% of drug after 12 hours, and the FTIR spectra reveals no interaction between drug and excipients in the formula. Most characteristics of risperidone nanovesicles was improved by adding dicetyl phosphate, compared with formulation without dicetyl phosphate. The main conclusion was that a stable nanovesicular system can be achieved by utilizing direct ultrasonication method and addition of charge inducing agent (dicetyl phosphate) without the need of using organic solvent.